2018
DOI: 10.1002/gj.3260
|View full text |Cite
|
Sign up to set email alerts
|

Mineral mapping using spaceborne Tiangong‐1 hyperspectral imagery and ASTER data: A case study of alteration detection in support of regional geological survey at Jintanzi‐Malianquan area, Beishan, Gansu Province, China

Abstract: This is an extension of our previous study and an applicability test on the mapping capability of Tiangong‐1 data with more complicated geological conditions over large areas. The Jintanzi‐Malianquan area is located in a major Au‐Cu‐Ni‐Cr resource belts in China. In order to support the 1:50,000 regional geological survey, this study presents the mapping results of using spectral angle mapper method and image endmembers from spaceborne Tiangong‐1 Hyperspectral Imager (HSI) shortwave infrared and Advanced Space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A correlation was established between identified alteration zones and known gold–copper deposits in the study area. The study by Liu et al ( ) is an extension of previous work on mineral mapping using spaceborne Tiangong‐1 hyperspectral imagery and ASTER data over a much wider and geologically more complex area near Beishan, Gansu Province. The region has important Au–Cu–Ni–Cr belts.…”
Section: Volume 3: Structure and Main Themesmentioning
confidence: 99%
“…A correlation was established between identified alteration zones and known gold–copper deposits in the study area. The study by Liu et al ( ) is an extension of previous work on mineral mapping using spaceborne Tiangong‐1 hyperspectral imagery and ASTER data over a much wider and geologically more complex area near Beishan, Gansu Province. The region has important Au–Cu–Ni–Cr belts.…”
Section: Volume 3: Structure and Main Themesmentioning
confidence: 99%
“…Two recent studies over sites in China described combined use of ASTER data with other, seldom-reported, remote sensing instruments. Liu et al [108] combined information from the Chinese hyperspectral scanner on the Tiangong-1 space station, with ASTER data for regional alteration mapping in the Jintanzi-Malianquan area. The hyperspectral instrument allowed detection of muscovite, kaolinite, chlorite, epidote calcite and dolomite, while ASTER data allowed detection of the first five, not dolomite.…”
Section: Alteration Mapping With Aster Data and Other Data Sourcesmentioning
confidence: 99%
“…Hyperspectral (HS) imaging is extensively used in earth observation satellites for various applications [1]: lithological mapping [2]- [6], environmental monitoring [7]- [9], and agricultural activities [10]- [12], since it captures more spectral information than its counterparts: multispectral and RGB imaging. However, HS images (HSIs) are of poor spatial resolution and are corrupted by noise and interference from atmospheric alterations and instrumentation imperfections [13].…”
Section: Introductionmentioning
confidence: 99%